2018
DOI: 10.1021/acs.nanolett.7b05339
|View full text |Cite
|
Sign up to set email alerts
|

Protein Nanosheet Mechanics Controls Cell Adhesion and Expansion on Low-Viscosity Liquids

Abstract: Adherent cell culture typically requires cell spreading at the surface of solid substrates to sustain the formation of stable focal adhesions and assembly of a contractile cytoskeleton. However, a few reports have demonstrated that cell culture is possible on liquid substrates such as silicone and fluorinated oils, even displaying very low viscosities (0.77 cSt). Such behavior is surprising as low viscosity liquids are thought to relax much too fast ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 38 publications
11
95
0
Order By: Relevance
“…F ad , adhesion force; F n and F t , forces applied by the cell in the normal and tangential directions, respectively. Reproduced with permission from Kong et al (2018a) where it was published under a Creative Commons Attribution license (CC BY 4.0). (E) HPKs cultured on fibronectin (Fn)-coated tissue culture plates (TPS-Fn, top) and protein nanoshets, assembled at either pH 7 (soft; middle) or pH 10 (stiff; bottom).…”
Section: Softmentioning
confidence: 99%
See 1 more Smart Citation
“…F ad , adhesion force; F n and F t , forces applied by the cell in the normal and tangential directions, respectively. Reproduced with permission from Kong et al (2018a) where it was published under a Creative Commons Attribution license (CC BY 4.0). (E) HPKs cultured on fibronectin (Fn)-coated tissue culture plates (TPS-Fn, top) and protein nanoshets, assembled at either pH 7 (soft; middle) or pH 10 (stiff; bottom).…”
Section: Softmentioning
confidence: 99%
“…Cells are even able to form stable adhesions and spread on substrates that lack bulk mechanical stability, such as the surface of liquids. The culture of cells on liquid-liquid interfaces has been demonstrated through the formation of a mechanically stable protein nanosheet (15-20 nm in thickness) at the interface (Kong et al, 2018a(Kong et al, ,b, 2017. These nanosheets are formed via pro-surfactantassisted self-assembly of proteins, and they enable cells to form mature FAs and to spread and to proliferate on the surface of liquid substrates (e.g.…”
Section: Nanoscale Mechanical Propertiesmentioning
confidence: 99%
“…At the interface between PFC and culture medium, protein film presumably forms as a rigid skin to which cells attach and spread. In these studies, however, an addition of crosslinking agents, such as, glutaraldehyde to the aqueous phase,[12a] reactive surfactants in the organic/oil phase, or the use of charge–charge interactions between protein and polylysine, was indispensable for cell spreading and proliferation. The free‐standing protein film situated at the interface substantially lacks vertical constraint and mechanical properties associated with bulk materials.…”
mentioning
confidence: 99%
“…Gautrot and co-workers reported the control of cell adhesion and expansion by protein nanosheet on low-viscosity liquids. [28] With addition of reactive surfactant pentafluorobenzoyl chloride, the mechanics of protein layer is enhanced, which can promote cell adhesion and proliferation. The same research team reported expansion and fate decision of stem cells with self-assembled nanosheets.…”
Section: Cells At Liquid Interfacementioning
confidence: 99%